The Effect of Credit Risk Management Strategies on Loan Recovery in Credit Cooperative Societies Saccos in Mukono District - Esther Jenipher Woor (Uganda Christian University, 2024)
The research investigates the effect of credit risk management strategies on credit recovery within the SACCOs in Mukono district. Specifically, it examines the effectiveness of risk avoidance, risk transfer, risk reduction and risk retention strategies in enhancing credit recovery outcomes. This research uses a descriptive survey as it provides a tool to contextually interpret and understand credit risk management strategies for credit recovery in SACCOs in Mukono district. Descriptive study describes the existing conditions and attitudes using the techniques of observation and interpretation. In survey research, the researcher selects a simple groupof respondents from a population and administers a standardized questionnaire to them. The questionnaire or survey can be a written document that is completed by respondent, an online questionnaire, a face-to-face interview or a telephone interview. The design will include an in depth study of credit risk management and its effect on credit recovery of SACCOs in Mukono district. The research found out that risk avoidance, risk transfer, risk reduction and risk retention strategies were instrumental in credit recovery processes. Saccos should fully adopt credit risk management strategies a means of reducing credit defaults. In particular, the management should consider implementing a framework approach to debt collection. The study finds that risk avoidance strategy such as stringent client appraisals and avoiding high risk borrowers significantly improve credit recovery by preventing problematic loans from entering the portfolio. Effective risk transfer mechanisms help enhance credit recovery by shifting some of the risks to other parties thus mitigating the financial Impact on SACCOs. Implemating robust risk reduction measures like continuous monitoring and updating positive collates with improved credit recovery hence minimizing defaults. The findings suggest that a comprehensive approach incorporating all the four strategies; risk avoidance, risk transfer, risk reduction and risk retention can significantly enhance credit recovery in SACCOs. Implementing a tailored mix of these strategies based on specific SACCO needs and contexts is recommended for optimal credit management